Seasonal influence of physicochemical parameters on phytoplankton diversity and assemblage pattern in Kailash Khal, a tropical wetland, Sundarbans, India - Pranab Gogoi; Archana Sinha; Soma Das Sarkar; Thangjam Nirupada Chanu; Anil Kumar Yadav; Satish Kumar Koushlesh; Simanku Borah; Sanjoy Kumar Das; Basanta Kumar Das (Applied Water Science, 2019)
Abstract Studies were carried out from April 2016 to March 2017 for effective understanding of diversity combined with environment-influenced spatiotemporal dynamics of microfloral structure in Kailash Khal wetland of Indian Sundarbans. A total of 36 phytoplankton genera were recorded from the study area. Eight major algal groups were in order of: Bacillariophyceae > Cyanophyceae > Chlorophyceae > Coscinodiscophyceae > Xanthophyceae > Euglenophyceae > Conjugatophyceae > Mediophyceae with respect to their quantitative abundance. Mean seasonal abundance was found highest in pre-monsoon (4.32 × 103 cells l−1) followed by post-monsoon (3.88 × 103 cells l−1) and monsoon (1.96 × 103 cells l−1). One-way ANOVA showed that seasonal difference in physicochemical parameters was statistically significant for temperature, DO, specific conductivity, TA, TS, Ca++, nitrate, transparency, salinity, TH, turbidity, Mg++ and phosphate (p < 0.05). pH, temperature, total hardness, TDS nitrate, phosphate and silicate showed a close affinity with the distribution of phytoplankton community as evident from canonical correspondence analysis. Margalef richness index (3.121–3.774) and Shannon–Wiener diversity index (2.730–2.939) indicated moderately rich phytoplankton diversity in the wetland ecosystem.